Metabolomic and transcriptomic analyses reveal the effects of grafting on blood orange quality - Yang, Lei; Chen, Yang; Wang, Min; Hou, Huifang; Li, Shuang; Guan, Ling; Yang, Haijian; Wang, Wu; Hong, Lin (Frontiers in Plant Science, 2023)
Blood orange (Citrus sinensis L.) is a valuable source of nutrition because it is enriched in anthocyanins and has high organoleptic properties. Grafting is commonly used in citriculture and has crucial effects on various phenotypes of the blood orange, including its coloration, phenology, and biotic and abiotic resistance. Still, the underlying genetics and regulatory mechanisms are largely unexplored. In this study, we investigated the phenotypic, metabolomic, and transcriptomic profiles at eight developmental stages of the lido blood orange cultivar (Citrus sinensis L. Osbeck cv. Lido) grafted onto two rootstocks. The Trifoliate orange “Zhiyang Xingcheng” rootstock provided the best fruit quality and flesh color for Lido blood orange. Comparative metabolomics suggested significant differences in accumulation patterns of metabolites and we identified 295 differentially accumulated metabolites. The major contributors were flavonoids, phenolic acids, lignans and coumarins, and terpenoids. Moreover, transcriptome profiling resulted in the identification of 4179 differentially expressed genes (DEGs), and 54 DEGs were associated with flavonoids and anthocyanins. Weighted gene co-expression network analysis identified major genes associated to 16 anthocyanins. Furthermore, seven transcription factors (C2H2, GANT, MYB-related, AP2/ERF, NAC, bZIP, and MYB) and five genes associated with anthocyanin synthesis pathway (CHS, F3H, UFGT, and ANS) were identified as key modulators of the anthocyanin content in lido blood orange. Overall, our results revealed the impact of rootstock on the global transcriptome and metabolome in relation to fruit quality in lido blood orange. The identified key genes and metabolites can be further utilized for the quality improvement of blood orange varieties.